2017
DOI: 10.1111/jgh.13727
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization prior to liver transplantation for patients with hepatocellular carcinoma: A meta‐analysis

Abstract: Background and Aim A debate exists over whether using preoperative transarterial chemoembolization for patients with hepatocellular carcinoma before liver transplantation. Numerous studies have been investigating on this, but there is still no unanimous conclusion about the effect of preoperative transarterial chemoembolization. We conducted the meta‐analysis of all available studies to systematically evaluate the influence of preoperative transarterial chemoembolization on liver transplant. Methods A systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 43 publications
0
17
0
1
Order By: Relevance
“…3 The five-year survival rate in HCC patients is only about 30%. 4 Hence, it is urgently required to investigate the in-depth mechanisms of HCC development.…”
Section: Introductionmentioning
confidence: 99%
“…3 The five-year survival rate in HCC patients is only about 30%. 4 Hence, it is urgently required to investigate the in-depth mechanisms of HCC development.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of neoadjuvant treatments on survival after liver transplantation are difficult to assess. Many studies reported similar survival rates between treated and untreated individuals prior to transplantation (253254255256257258259). Patients who received locoregional treatments before liver transplantation in Organ Procurement and Transplantation Network/Scientific Registry of Transplant Recipients were more likely to achieve longer survival than those who did not, particularly those with longer waiting periods before transplantation (260).…”
Section: Liver Transplantationmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is a major health problem worldwide 1,2. It affects more than 500,000 people worldwide every year,3 with a 5-year survival rate of 30% 4. The poor prognosis is mainly attributed to a high rate of recurrence and metastasis 5…”
Section: Introductionmentioning
confidence: 99%